2019
DOI: 10.1016/j.jse.2018.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Validity and efficiency of a smartphone-based electronic data collection tool for operative data in rotator cuff repair

Abstract: Purpose-This study tested validity and efficiency of Orthopaedic Minimal Data Set (OrthoMiDaS) Episode of Care (OME).Methods-100 isolated rotator cuff repair cases in the OME database were analyzed. Surgeons completed a traditional operative note and OME report. A blinded reviewer extracted data from operative notes and implant logs in electronic medical records by manual chart review. OME and EMR data were compared with data counts and agreement between 40 variables of rotator cuff pathology and repair proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…Data on 20 of the 24 preoperative patient and disease-specific factors were obtained from the Cleveland Clinic's OME database, 5 which is approved by Cleveland Clinic's institutional review board (#06-196) and has been shown to be a valid and efficient tool for collecting comprehensive and standardized data on RCR. 26 Data on 4 factors (comorbidities, preoperative opioid use, chronic pain, and workers' compensation status) were obtained from the Cleveland Clinic's electronic medical record (EMR) (Epic Systems), Perioperative Health Documentation System database, and Epic Cost of Goods Sold system. The CCI was calculated from the comorbidity data.…”
Section: Data Sourcementioning
confidence: 99%
“…Data on 20 of the 24 preoperative patient and disease-specific factors were obtained from the Cleveland Clinic's OME database, 5 which is approved by Cleveland Clinic's institutional review board (#06-196) and has been shown to be a valid and efficient tool for collecting comprehensive and standardized data on RCR. 26 Data on 4 factors (comorbidities, preoperative opioid use, chronic pain, and workers' compensation status) were obtained from the Cleveland Clinic's electronic medical record (EMR) (Epic Systems), Perioperative Health Documentation System database, and Epic Cost of Goods Sold system. The CCI was calculated from the comorbidity data.…”
Section: Data Sourcementioning
confidence: 99%
“…Irrespective of the rapid developments in the field of medical apps, young physicians especially have experienced a fundamental change in their information behavior over the past few years [16]. An increasing number of studies have focused on the benefits and consequences of smartphone use in the fields of orthopedics and trauma surgery [17][18][19][20][21][22]. Today, the majority of American orthopedic surgeons use smartphones and a wide variety of apps in their daily clinical work [23].…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of rapid developments in the field of medical apps, the information behavior of young physicians has fundamentally changed in recent years [13]. Numerous studies have focused on the potential benefits and consequences of smartphone usage in the fields of orthopedic surgery as a result of the rapidly growing mobile health (mHealth) implementation [14][15][16][17][18]. Currently, there are some app store-based screening reviews of commercially available apps that have been developed to address daily clinical issues in orthopedics [19,20].…”
Section: Mobile Health In Orthopedic Surgeons Clinical Usementioning
confidence: 99%